Challenges on Radical Health Redesign to Reconfigure the Level of e-Health Adoption in EU Countries - Luca, Magda Mihaela; Mustea, Lavinia; Taran, Alexandra; Stefea, Petru; Vatavu, Sorana (Frontiers in Public Health, 2021)
The recent worldwide COVID-19 pandemic highlighted the importance of a performant public sector in terms of health. To achieve greater use and efficiency of health information and communication technology (ICT), the whole community of European states needs a model to develop a common strategy to support the implementation of e-health and reduce decision-making difficulties. Our research suggests such a model, starting from the level of adoption and implementation of e-health and the existing disparities in European countries regarding the difficulties of adopting e-health. We draw a composite index to assess the inequalities present in the quality of life, the public health system and the adoption of e-health. Furthermore, to return a hierarchy of European countries, the relative distances method is applied by combining various classification criteria. The results identify the European countries with the highest levels of adoption (Denmark, Estonia, Spain, Sweden, Finland, and the United Kingdom), where e-health is routine, and the countries with the lowest levels of adoption (Greece, Lithuania, Luxembourg, Malta, Romania, and Slovakia), where e-health is not widespread. These results reveal critical implications in identifying solutions to reduce the gaps between countries, identifying public policies to support the adoption of e-health, and reducing difficulties in decision-making.